FAKTOR DETERMINAN PENINGKATAN STATUS GIZI BAYI UMUR 6-11 BULAN PADA KELUARGA MISKIN YANG MEMPEROLEH BLENDED FOOD DI KECAMATAN PEDURUNGAN - Sunarto . .; Teguh . Budiharjo (Jurnal Kesehatan Masyarakat Indonesia, 2004)
ABSTRACT Background: A study conducted by Purwaningsih (2002) revealed that giving added supplement l00 formula for malnourished babies can only increase the Z score of baby's body weight/ age from -3.5 to -3.18 Objective: This case-control study is aimed at researching determinant factors of nutritional 6-ll month old babies in poor families that are given blended food. Method: Samples of this research comprise 76 babies of 6-l I months old which can be divided into two groups, firstly 38 babies for the case group and the rest is for the control group. Result: (t) Statistics correlation between vitamin A status and the increase of Z Score after being controlled by immunization status, frequency of health care utility, educational background of baby's mother and father, pattern of care, and utility of posyandu, is not significantly proven. There is also no correlation between baby immunization status,-utility of posyandu, educational of baby's father and mother and the increase of Z Score, after being controlled by other variables.(2) There is statistically significant correlation between pattern of care the increase of Z Score after being controlled by vitamin A status, frequency of health care utility, utility of posyandu, educational background of baby's mother and father, pattern of care, and baby immunization status. There are also correlations between frequency of health care utility and the increase of Z score after being controlled by other variables. Conclusion: Determinant factors of increasing nutritional status for baby in poor families are pattern of care and frequency of health care after being controlled by other variables. Key Words: Nutritional status, poor family's babies, blended food